Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm studying for my linear algebra exam and I came across this exercise that I can't solve.

Find all roots of polynomial $x^{6} + 1$. Hint: use De Moivre's formula.

I guessed that two roots are $i$ and $-i$, since:

$i^{6} = (i^{2})^{3} = (-1)^{3} = -1 $

therefore, $i$ is root and his complex conjugate $-i$ has to be root too. However that was just guessing. I have no idea how can I use De Moivre's formula here.

Can you help me solve this?

share|improve this question

4 Answers 4

up vote 6 down vote accepted

Hint: if $x^6=-1$, then $|x|^6=1$ and you can write $x=\cos\theta + i\sin\theta$.

details:

Then the equation is, thanks to De Moivre theorem and $\cos^2 + \sin^2 =1$, equivalent to $$ \cos 6\theta =-1\\ 6\theta = \pi\mod 2\pi\\ \theta\in \frac \pi 6+\left\{0, \frac\pi 3, \frac{2\pi}3,\pi,\frac{4\pi} 3, \frac{5\pi}3 \right\}. $$

share|improve this answer
1  
Watch it: the equation is $\;x^6+1=0\iff x^6=\color{red}-1\;$ ... –  DonAntonio Mar 29 at 15:57
    
Check also the values of $\;\theta\;$, @mookid ... –  DonAntonio Mar 29 at 16:00
    
@mookid this doesn't yield either $i$ or $-i$, you might want to check your calculation. –  Sabyasachi Mar 29 at 16:02
    
@mookid yes it is. –  Sabyasachi Mar 29 at 16:05
    
Of course, simple and elegant. Thank you –  xerwin Mar 29 at 16:09

I'd like to add that this is possible to solve using well known formulas for $x^n\pm a^n$: $$\begin{align}x^6+1&=(x^3)^2-i^2=(x^3+i)(x^3-i)=(x^3-i^3)(x^3+i^3)\\&=(x-i)(x^2+ix+i^2)\cdot(x+i)(x^2-ix+i^2)\end{align}$$

And now you can use the formula for quadratic roots to get them all in an explicit form.

share|improve this answer
    
Also,$x^6+1=(x^2)^3+1^3=(x^2+1)(x^4+x^2+1)=0$. Now we have to solve two quadratic equations to obtain the required roots. –  rah4927 Mar 29 at 16:59

If $z^6 + 1= 0$ then $z^6 = -1$. We can write $-1 = \mathrm{e}^{\mathrm{i}(\pi+2\pi n)}$ where $n \in \mathbb{Z}$. It follows that $$(-1)^{1/6} = \{\mathrm{e}^{\mathrm{i}(\pi/6+\pi n/3)} : n \in \mathbb{Z}\}$$ Putting $n=0,1,2,3,4,5$ will give you all of the solutions you need. For example, when $n=1$: $$z = \mathrm{e}^{\mathrm{i}(\pi/6+\pi /3)} = \mathrm{e}^{\mathrm{i}(\pi/2)} = \cos\tfrac{\pi}{2}+\mathrm{i}\sin\tfrac{\pi}{2} = \mathrm{i}$$

share|improve this answer

The easiest way to do these problems is using the polar form of a complex number.

$$ x^6 + 1 = 0 \rightarrow x^6 = -1 $$

Write $-1$ as a complex number in polar form with the $+2\pi n$ (the most general form), then write $x$ as a general complex number:

$$ \left(re^{i\theta}\right)^6 = 1e^{\pi i + 2\pi n i} \\ r^6 e^{6\theta i} = 1 e^{\left(\pi + 2\pi n\right)i} $$

From here, $r = 1$ (because $x^6 = 1$ has only one real root: $x = \sqrt[6]{1} = 1$). Then you just set the angles equal:

$$ 6\theta = \pi + 2\pi n \\ \theta = \frac{\pi + 2\pi n}{6} = \frac{\pi}{6} + \frac{\pi}{3}n $$

Now just keep incrementing $n$ until you start looping (which will happen after $6$ consecutive values of $n$):

$$ \theta = \frac{\pi}{6}, \frac{\pi}{6} + \frac{\pi}{3}, \frac{\pi}{6} + \frac{2\pi}{3}, ... $$

If you want to write them as $a +bi$ then you have to convert each of those to $r\cos(\theta) + ri\sin(\theta)$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.